Fuel cell separator component and method for manufacturing the same
By adopting a combined structure of the first resin layer and the graphite layer in the partition member for fuel cell, the problem of low toughness of the expanded graphite sheet is solved, and the effect of thin graphite layer and excellent conductivity is achieved, and the strength of the partition is improved. and conductivity.
Patent Information
- Application Number
- CN202180038800.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-05
- Filing Date
- 2021-05-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-05-20
AI Technical Summary
The conventional fuel cell separator component includes an expanded graphite sheet, which leads to a low toughness and a decrease in strength of the graphite sheet.
The first resin layer composed of resin and the graphite layer formed substantially from graphite are used, the layering amount of the graphite layer is 50 g/m2 or less, and the volume resistivity of graphite is 3 mΩ·cm or less.
It provides a partition member for fuel cell with a thin graphite layer thickness and excellent conductivity, which improves the overall strength and conductivity of the partition.
Smart Images

Figure CN115699372B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a separator member for a fuel cell and a method for producing the same. Background Art
[0002] The properties required of a fuel cell separator member include electrical conductivity, air impermeability (also referred to as gas barrier properties), etc. As materials for improving the electrical conductivity of a fuel cell separator member, conductive materials such as carbon black, expanded graphite, and natural graphite can be cited. In addition, various fuel cell separator members using such conductive materials have been proposed (for example, see Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2009-129601 Summary of the invention
[0006] Problems to be solved by the invention
[0007] The preform constituting the fuel cell separator disclosed in Patent Document 1 is constituted by an expanded graphite sheet. The expanded graphite sheet is relatively thick and has low toughness, so there is a problem that the strength of the preform including the expanded graphite sheet is reduced.
[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a fuel cell separator member having a thin graphite layer and excellent electrical conductivity, and a method for producing the same.
[0009] Means for solving problems
[0010] The inventors of the present application have conducted intensive research to solve the above-mentioned problems. As a result, they have found that the following fuel cell separator component can solve the above-mentioned problems, thereby completing the present invention. The fuel cell separator component includes a first resin layer composed of resin, and a graphite layer laminated on the first resin layer and substantially composed of graphite, wherein the lamination amount of the graphite layer is 50 g / m 2 Below, the volume resistivity of graphite is 3 mΩ·cm or less.
[0011] That is, the present invention is as follows.
[0012] [1] A fuel cell separator member comprising: a first resin layer composed of a resin; and a graphite layer laminated on the first resin layer and substantially composed of graphite, wherein the lamination weight of the graphite layer is 50 g / m 2 Hereinafter, the volume resistivity of the graphite is 3 mΩ·cm or less.
[0013] [2] A fuel cell separator component as described in [1] above, wherein a conductive fiber substrate and a second resin layer composed of resin are stacked in sequence from the first resin layer side between the first resin layer and the graphite layer, and the thickness of the second resin layer is thinner than that of the first resin layer.
[0014] [3] The fuel cell separator member according to [1] or [2] above, wherein the resin is a thermoplastic resin composition or a thermosetting resin composition.
[0015] [4] A method for manufacturing a separator member for a fuel cell, comprising: a first resin layer forming step of forming a first resin layer composed of a resin; and a graphite layer forming step of forming a graphite layer on the first resin layer, wherein the lamination weight of the graphite layer is 50 g / m 2 The graphite material is substantially composed of graphite having a volume resistivity of 3 mΩ·cm or less.
[0016] [5] A method for manufacturing a fuel cell separator component as described in [4] above, wherein the graphite layer forming step includes: a graphite sheet laminating step, laminating a graphite sheet formed of the graphite on the first resin layer and crimping the graphite sheet; and a peeling step, peeling the graphite sheet after the graphite sheet laminating step.
[0017] [6] A method for manufacturing a fuel cell separator component as described in [4] or [5] above, wherein the first resin layer forming step includes: a resin coating step of coating the resin on a film subjected to a demolding treatment; and a resin curing step of forming the first resin layer in a semi-cured state.
[0018] [7] A method for manufacturing a separator component for a fuel cell, comprising: a resin coating step of coating a resin on a film subjected to a demolding treatment; a first resin layer forming step of curing the resin to a semi-cured state to form a first resin layer; a graphite sheet laminating step of laminating a graphite sheet formed of graphite having a volume resistivity of 3 mΩ·cm or less on the first resin layer and crimping the graphite sheet; a film peeling step of peeling the film from the first resin layer; a second graphite sheet laminating step of laminating a graphite sheet formed of graphite having a volume resistivity of 3 mΩ·cm or less on the surface of the first resin layer from which the film has been peeled and crimping the graphite sheet; and a peeling step of peeling the graphite sheet from both sides of the first resin layer.
[0019] [8] A method for manufacturing a separator member for a fuel cell, comprising:
[0020] The first resin layer forming step forms a first resin layer composed of resin; the second resin layer forming step forms a second resin layer composed of resin and thinner than the first resin layer in a semi-cured state; the conductive fiber substrate laminating step laminating a conductive fiber substrate on the second resin layer and performing heat compression bonding; the graphite layer forming step forms a graphite layer on the resin surface of the second resin layer on which the conductive fiber substrate is laminated, wherein the lamination weight of the graphite layer is 50 g / m 2 and a first resin layer laminating step of laminating the first resin layer on the conductive fiber substrate of the second resin layer and performing heating and pressurization.
[0021] [9] A method for manufacturing a fuel cell separator component as described in [8] above, wherein the first resin layer forming step includes: a resin coating step of coating the resin on a film subjected to a mold release treatment; and a resin curing step of forming the first resin layer in a semi-cured state.
[0022]
[10] A method for manufacturing a fuel cell separator component as described in [8] or [9] above, wherein the second resin layer forming step includes: a second resin coating step of coating the resin on a film that has been subjected to a demolding treatment; and a second resin curing step of forming a second resin layer in a semi-cured state.
[0023]
[11] A method for manufacturing a fuel cell separator component as described in any one of [8] to
[10] above, wherein the graphite layer forming step includes: a graphite sheet stacking step, stacking a graphite sheet formed from the graphite on a resin surface of a second resin layer stacked with the conductive fiber substrate and crimping the stacked graphite sheet; and a peeling step, peeling the graphite sheet after the graphite sheet stacking step.
[0024] Effects of the Invention
[0025] According to the present invention, it is possible to provide a fuel cell separator member having a thin graphite layer and excellent electrical conductivity, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] [ Figure 1 ] is a schematic cross-sectional view showing the structure of a separator component for a fuel cell according to Embodiment 1.
[0027] [ Figure 2] are figures illustrating the process of manufacturing a fuel cell partition member according to embodiment 1, (a) is a figure illustrating the process of coating a resin constituting a first resin layer, (b) is a figure illustrating the process of drying the first resin layer, (c) is a figure illustrating the process of stacking graphite sheets on both sides of the first resin layer, and (d) is a figure illustrating the process of peeling off graphite sheets from both sides of the first resin layer to form a stacked body.
[0028] [ Figure 3 ] is a schematic cross-sectional view showing the structure of a separator component for a fuel cell according to Embodiment 2.
[0029] [ Figure 4A ] are figures illustrating the process of manufacturing a fuel cell partition member according to embodiment 2, (a) is a figure illustrating the process of applying a resin constituting a first resin layer, (a-1) is a figure illustrating the process of drying the first resin layer, (b) is a figure illustrating the process of applying a resin constituting a second resin layer, and (b-1) is a figure illustrating the process of drying the resin.
[0030] [ Figure 4B ] is a figure illustrating the process of manufacturing the fuel cell partition component of embodiment 2, (c) is a figure illustrating the process of stacking a conductive fiber substrate on the second resin layer and crimping it, (d) is a figure illustrating the process of stacking a graphite sheet on the second resin layer obtained in the (c) process and crimping it, and (e) is a figure illustrating the process of stacking a first resin layer on the conductive fiber substrate of the second resin layer and crimping it.
[0031] [ Figure 4C ] is a diagram illustrating the process of manufacturing a separator component for a fuel cell according to Embodiment 2, and (f) is a diagram illustrating the process of peeling off a graphite sheet from a laminate. DETAILED DESCRIPTION
[0032] Hereinafter, the fuel cell separator component and the manufacturing method thereof according to the embodiment of the present invention will be described in detail. The following embodiments are examples for illustrating the present invention, and the main purpose is not to limit the present invention to the following contents. The present invention can be appropriately modified and implemented within the scope of its main purpose.
[0033] The fuel cell separator member of the present invention can be suitably used as a member constituting a separator of a fuel cell. The fuel cell separator member referred to in the present invention refers to a member before being processed into a fuel cell separator.
[0034] (Implementation Method 1)
[0035] (Configuration of Fuel Cell Separator Member 10)
[0036] The fuel cell separator member 10 of the first embodiment includes a first resin layer made of resin and a graphite layer laminated on the first resin layer and substantially made of graphite, wherein the lamination weight of the graphite layer is 50 g / m 2 Below, the volume resistivity of graphite is 3 mΩ·cm or less.
[0037] Figure 1 1 is a schematic cross-sectional view showing a fuel cell separator member 10. The fuel cell separator member 10 has a structure in which graphite layers 11 are laminated on both surfaces of a first resin layer 13.
[0038] The first resin layer 13 is made of resin. The type of resin is not particularly limited as long as it can form the first resin layer 13 of the fuel cell separator component and can process the fuel cell separator component to form a fuel cell separator. Examples of the resin include thermosetting resin compositions and thermoplastic resin compositions.
[0039] As the thermosetting resin composition, epoxy resin compositions with epoxy resin as the main agent, phenolic resin compositions with phenolic resin as the main agent, polyimide resin compositions with thermosetting polyimide resin as the main agent, melamine resin compositions with melamine resin as the main agent, polyurethane resin compositions with polyurethane resin as the main agent, diallyl phthalate resin compositions with diallyl phthalate resin as the main agent, unsaturated polyester resin compositions with unsaturated polyester resin as the main agent, and cyanate resin compositions with cyanate resin as the main agent can be cited. From the viewpoints of heat resistance, durability, and processability, and the viewpoint of the adhesion between the first resin layer 13 and the graphite layer 11, epoxy resin compositions are preferred.
[0040] Examples of the thermoplastic resin composition include acrylic resin compositions mainly composed of acrylic resins, polyacrylonitrile resin compositions mainly composed of polyacrylonitrile resins, polyimide resin compositions mainly composed of thermoplastic polyimide resins, polyamide resin compositions mainly composed of polyamide resins, polyethersulfone resin compositions mainly composed of polyethersulfone resins, phenoxy resin compositions mainly composed of phenoxy resins, polypropylene resin compositions mainly composed of polypropylene resins, polycarbonate resin compositions mainly composed of polycarbonate resins, polyethylene resin compositions mainly composed of polyethylene resins, polyester resin compositions mainly composed of polyester resins, acrylonitrile-butadiene-styrene resin compositions mainly composed of acrylonitrile-butadiene-styrene (ABS) resins, polystyrene resin compositions mainly composed of polystyrene (PS) resins, polyphenylene sulfide resin compositions mainly composed of polyphenylene sulfide (PPS) resin compositions, and polyamideimide resin compositions mainly composed of polyamideimide (PAI) resins. From the viewpoints of heat resistance, durability, and processability, and the viewpoint of adhesion between the first resin layer 13 and the graphite layer 11 , a polyethersulfone-based resin composition and a polypropylene-based resin composition are preferred.
[0041] From the viewpoint of improving the conductivity of the fuel cell separator member 10, a conductive material may be added to the resin of the first resin layer 13. As the conductive material, for example, artificial graphite, natural graphite, carbon black, carbon fiber, carbon nanotube (CNT) may be cited. From the viewpoint of conductivity and cost, artificial graphite and / or natural graphite are preferably used.
[0042] The amount of the conductive material added is preferably 40 to 90 parts by mass, more preferably 60 to 90 parts by mass, and even more preferably 60 to 85 parts by mass, based on 100 parts by mass of the total resin in terms of solid content, from the viewpoint of processability.
[0043] The thickness of the first resin layer 13 depends on the thickness of the fuel cell separator itself, and is preferably 100 to 800 μm, and is 100 to 700 μm from the viewpoint of lightness and processability.
[0044] The graphite constituting the graphite layer 11 is not particularly limited, but natural graphite is preferred from the viewpoint of suppressing the volume resistivity to be low, and expanded graphite is more preferred from the viewpoint of being able to form the graphite layer with a uniform and thin thickness.
[0045] From the viewpoint of ensuring the electrical conductivity of the fuel cell separator, the volume resistivity of graphite is preferably 3 mΩ·cm or less, and more preferably 1 mΩ·cm or less.
[0046] From the viewpoint of lightness and processability, the lamination weight of the graphite layer 11 is 50 g / m2 Below, preferably 0.3 to 50 g / m 2 , more preferably 0.5 to 30 g / m 2 .
[0047] From the viewpoint of electrical conductivity and processability, the thickness of the graphite layer 11 is preferably 0.1 μm to 50 μm. From the viewpoint of electrical conductivity and thinness, it is more preferably 0.2 μm to 15 μm. It should be noted that the thickness of the graphite layer 11 refers to the thickness of the graphite layer after the fuel cell separator member 10 is processed into a fuel cell separator.
[0048] The graphite layer 11 is substantially formed of graphite. The term "substantially formed of graphite" means that the amount of non-conductive material present in the graphite layer 11 is so small that it does not hinder the conductivity of the fuel cell separator member 10. Specifically, it means that the volume resistivity of the graphite is 3 mΩ·cm or less, and the material constituting the graphite layer 11 is composed of 95 wt% or more of graphite.
[0049] The fuel cell separator component 10 of Embodiment 1 is described by taking the configuration in which the graphite layers 11 are stacked on both surfaces of the first resin layer 13 as an example, but the fuel cell separator component 10 may also be a configuration in which the graphite layer 11 is stacked on only one surface of the first resin layer 13 .
[0050] As another embodiment of the separator component 10 for fuel cells, other layers may be stacked between the first resin layer 13 and the graphite layer 11. The other layers may be single layers or multiple layers. For example, when it is a single layer, the resin constituting the single layer may be the same as or different from the resin constituting the first resin layer 13. When the resin constituting the single layer is different from the resin constituting the first resin layer 13, the resin constituting the first resin layer 13 is composed of a thermoplastic resin composition, and the other layers are composed of a thermosetting resin composition. As a result, the followability of the mold is improved when the separator component 10 for fuel cells is processed into a separator for fuel cells.
[0051] (Method for Manufacturing Fuel Cell Separator Member 10)
[0052] The method for manufacturing the fuel cell separator member 10 comprises: a first resin layer forming step of forming a first resin layer 13 composed of a resin; and a graphite layer forming step of forming a graphite layer with a lamination weight of 50 g / m 2The graphite layer 11 substantially formed of graphite having a volume resistivity of 3 mΩ·cm or less is as follows. In addition, the first resin layer forming step includes: a resin coating step of coating a resin on the film subjected to the demolding treatment; and a resin curing step of forming a semi-cured first resin layer 13. In addition, the graphite layer forming step includes: a graphite sheet laminating step of laminating a graphite sheet formed of graphite on the first resin layer 13 and pressing it; and a peeling step of peeling the graphite sheet from the first resin layer 13 after the graphite sheet laminating step.
[0053] Figure 2 1 is a diagram for explaining a method for manufacturing a fuel cell separator member 10. Figure 2 (a) The resin coating process is described. The coating device 201 coats the resin constituting the first resin layer 203 on the demolding-treated surface of the film 205 that has been subjected to the demolding treatment. It is preferred that the demolding treatment be applied to at least one surface of the film 205. The film 205 is not particularly limited as long as it can be peeled off from the first resin layer 203 after solidification. Examples of the material of the film 205 include plastics such as polyethylene terephthalate, polyethylene, and polypropylene, and paper. Examples of materials used in the demolding treatment include silicone-based materials, fluorine-based materials, and the like. The coating device 201 is not particularly limited, and a known coating device can be used. For example, a die coater, a comma coater, a gravure coater, and the like can be used. Examples of the coating method include, for example, Figure 2 (a) shows a method in which the coating device 201 is moved to coat the resin on the film 205, and a method in which the film 205 is moved to coat the resin.
[0054] Reference Figure 2 (b) The resin curing process is described. The first resin layer 203 is dried to a semi-cured state (B stage state). For drying, a dryer is used. The first resin layer 203 is preferably dried by heating. The heating and drying conditions can be appropriately selected according to the thickness of the first resin layer 203. For example, it is 40 to 200°C and 1 to 120 minutes. The surface of the dried first resin layer 203 may be sticky (tacky). As a result, the adhesion between the graphite sheet 207 used in the subsequent graphite sheet lamination process and the first resin layer 203 becomes good. Here, the semi-cured state (also called the B stage state) refers to a state in which the curing reaction of the resin is not completely carried out. Hereinafter, the "semi-cured state" used in the specification is also used with the same meaning.
[0055] From the viewpoint of improving the shape followability of the mold used for forming the fuel cell separator and the viewpoint of ensuring uniform thickness, the thickness of the first resin layer 203 is preferably 100 μm or more. For example, when the thickness of the fuel cell separator component is several hundred μm, as an example, two 100 μm first resin layers 203 are prepared and the resin surfaces are bonded to each other, thereby obtaining a first resin layer 203 with a thickness of 200 μm. As another example, three or more first resin layers 203 with a thickness of 50 to 100 μm are prepared and stacked and bonded, thereby obtaining a first resin layer 203 with a thickness of several hundred μm.
[0056] Reference Figure 2 (c) describes the graphite sheet lamination process. The film 205 is peeled off from the first resin layer 203 in a semi-cured state. Graphite sheets 207 are stacked on both sides of the first resin layer 203 and pressed together by roller 209. Roller 209 moves along the surface direction of the stack 206. The stack 206 can also be moved and pressed together by rollers. After pressing together, the stack 206 is obtained. Pressing can be performed at room temperature. From the viewpoint of improving the adhesion between the first resin layer 203 and the graphite sheet 207, pressing can be performed while heating.
[0057] In addition to the method using the roller 209, for example, a method using a press machine may be used. The pressing may be performed at room temperature or while being heated. The conditions for heating and pressing may be appropriately selected according to the thickness of the graphite sheet 207 and the thickness of the first resin layer 203. For example, it may be performed under the conditions of 20 to 200°C and 0.1 to 20 MPa.
[0058] In the graphite sheet lamination step, the graphite sheets 207 may be laminated and pressed on both sides of the first resin layer 203. For example, the graphite sheet 207 may be laminated and pressed on the resin surface of the first resin layer 203 after the resin curing step. Then, the film 205 may be peeled off, and the graphite sheet 207 may be laminated and pressed on the resin surface of the exposed first resin layer 203.
[0059] As the graphite sheet 207, there can be mentioned a natural graphite sheet obtained by forming natural graphite into a sheet without using a binder or an additive, or an artificial graphite sheet obtained by sintering an organic film such as polyimide. The so-called natural graphite sheet refers to a graphite sheet obtained by subjecting natural graphite to an acid treatment, rapidly heating it to a high temperature (e.g., 900 to 1000° C.), and compressing the expanded natural graphite. From the viewpoint of reducing the volume resistivity and making the stacking amount uniform, the graphite sheet 207 used is preferably a natural graphite sheet.
[0060] Reference Figure 2(d) The peeling process is described. The peeling method of the graphite sheet 207 is any method in which the graphite sheet 207 is peeled off from the laminate 206 to form the graphite layer 210 on the surface of the first resin layer 203. For example, a peeling method in which only the graphite sheet 207 is peeled off from the end of the laminate 206 can be cited. After the graphite sheet 207 is peeled off from the laminate 206, a graphite layer 210 with a stacking amount of 50 g / m2 is formed on both sides of the first resin layer 203. 2 The graphite layer 210 is substantially formed of graphite having a volume resistivity of 3 mΩ·cm or less. The stack 220 formed with the graphite layer 210 corresponds to the fuel cell separator member 10. The graphite layer 210 corresponds to Figure 1 The graphite layer 11 of the fuel cell separator member 10 is shown. The first resin layer 203 corresponds to the first resin layer 13. It should be noted that the graphite sheet 207 peeled off from the first resin layer 203 can be used multiple times as long as it is not damaged.
[0061] As another method of forming the graphite layer 210, a graphite sheet 207 may be wound around the outer circumference of a roller and fixed, and the roller may be used to press the first resin layer 203 to form the graphite layer 210. In addition, by this method, the first resin layer forming step and the graphite layer forming step can be combined into one line, and the fuel cell separator member 10 can be continuously manufactured.
[0062] As other methods for forming the first resin layer 203, there are: a method of forming the first resin layer 203 by stretching a solvent-free resin having adjusted viscosity into a film; and a method of depositing a fibrous resin on a film-like substrate by a papermaking method to form the first resin layer 203. According to these methods, the first resin layer 203 does not contain a solvent, so that processing becomes easy.
[0063] As another method for manufacturing the separator component 10 for a fuel cell, the following method can be cited, which comprises: a laminating step of laminating the adhesive surface of the adhesive film to the graphite sheet; a step of preparing the adhesive film with a graphite layer, peeling the adhesive film from the graphite sheet to obtain the adhesive film with a graphite layer; a step of forming a first resin layer, forming a first resin layer composed of a resin; a laminating and pressing step, laminating and pressing the two sides of the first resin layer obtained in the first resin layer forming step in such a way that the graphite layer of the adhesive film with a graphite layer contacts therewith; and a step of peeling off the adhesive film from the laminate obtained by the laminating and pressing step. According to this manufacturing method, even in the case where the first resin layer is easily broken or the first resin layer is difficult to handle, the separator component 10 for a fuel cell can be manufactured without destroying the shape of the first resin layer.
[0064] The manufacturing method of the separator component 10 for a fuel cell in which a graphite layer 11 is formed on any one surface of the first resin layer 13, for example, comprises: a resin coating step of coating a resin on a film subjected to a demolding treatment; a resin curing step of forming a first resin layer in a semi-cured state; a graphite sheet lamination step of laminating a graphite sheet formed of graphite on the first resin layer and crimping it; and a peeling step of peeling the graphite sheet after the graphite sheet lamination step. Thus, the separator component 10 for a fuel cell in which a graphite layer 11 is formed on one side of the first resin layer 13 can be obtained. The separator component 10 for a fuel cell in which a graphite layer 11 is formed on any one surface of the first resin layer 13 is not limited to the exemplified method, and can be manufactured by applying other methods.
[0065] According to the structure of the fuel cell separator member 10, after the fuel cell separator member 10 is processed into a fuel cell separator, there is no unevenness on the surface of the fuel cell separator due to expansion. In addition, it is easy to process the fuel cell separator member 10 into a fuel cell separator. The mechanism inferred by the inventor of the present application regarding the non-expansion of the fuel cell separator and the excellent processability of the fuel cell separator member 10 is explained.
[0066] When the graphite layer 11 of the fuel cell separator member 10 is observed from above, the graphite layer 11 is in a state where the graphite is arranged irregularly. It is speculated that this state is formed when the graphite sheet is peeled off. In addition, it is also believed that the irregular arrangement of graphite is also caused by the shape of the graphite. The shape of graphite is a thin sheet with a main surface. Due to such a shape, on the surface of the graphite layer, some graphites are in a state where the main surface of the graphite is arranged roughly parallel to the XY plane (the main plane of the graphite layer). Other graphites are in a state where the main surface of the graphite is perpendicular to the XY plane. In addition, some graphites are in a state where the main surface of the graphite is inclined relative to the XY plane, that is, the main surface of the graphite has an angle relative to the XY plane. In this way, it is speculated that there is a mixture of graphites with the main surface facing various directions on the surface of the graphite layer 11. In addition, such an irregular arrangement of graphite and the thin thickness of the graphite layer 11 complement each other, so that the gas generated during the curing of the first resin layer will not remain between the graphite layer 11 and the first resin layer 13 but will be released openly. As a result, it is estimated that no expansion occurs in the fuel cell separator member.
[0067] In addition, the graphite constituting the graphite layer 11 has mold release properties, so there is no need to use a mold release agent to facilitate mold release between the fuel cell separator member 10 and the molding mold. In this way, since a mold release agent is not required, the decrease in the hydrophilicity of the fuel cell separator itself caused by the mold release agent can also be suppressed.
[0068] In addition, at the interface between the graphite layer 11 and the first resin layer 13 and in the vicinity of the interface, a region where the resin constituting the first resin layer 13 and graphite are mixed is formed due to pressure bonding during the manufacturing process. It is estimated that this improves the adhesion between the graphite layer 11 and the first resin layer 13.
[0069] (Implementation Method 2)
[0070] (Configuration of Fuel Cell Separator Member 30)
[0071] The fuel cell separator member 30 of the second embodiment comprises: a first resin layer composed of resin; and a graphite layer substantially composed of graphite. Between the first resin layer and the graphite layer, a conductive fiber substrate and a second resin layer composed of resin are stacked in order from the first resin layer side. The thickness of the second resin layer is thinner than that of the first resin layer. The stacking amount of the graphite layer is 50 g / m 2 Below, the volume resistivity of graphite is 3 mΩ·cm or less.
[0072] Figure 3 1 is a schematic cross-sectional view showing an example of a fuel cell separator member 30 according to Embodiment 2. The fuel cell separator member 30 has the following structure: a conductive fiber substrate 35, a second resin layer 33, and a graphite layer 31 are stacked on both sides of a first resin layer 37 in order from near to far from the first resin layer 37.
[0073] The first resin layer 37 has the same structure as the first resin layer 13 of the fuel cell separator member 10 .
[0074] The second resin layer 33 is made of resin. The type of resin is not particularly limited. Examples of the resin include thermosetting resin compositions and thermoplastic resin compositions.
[0075] As the thermosetting resin composition, epoxy resin compositions with epoxy resin as the main agent, phenolic resin compositions with phenolic resin as the main agent, polyimide resin compositions with thermosetting polyimide resin as the main agent, melamine resin compositions with melamine resin as the main agent, polyurethane resin compositions with polyurethane resin as the main agent, diallyl phthalate resin compositions with diallyl phthalate resin as the main agent, unsaturated polyester resin compositions with unsaturated polyester resin as the main agent, and cyanate resin compositions with cyanate resin as the main agent can be cited. From the viewpoints of heat resistance, durability, and processability, epoxy resin compositions are preferred.
[0076] Examples of the thermoplastic resin composition include acrylic resin compositions mainly composed of acrylic resins, polyacrylonitrile resin compositions mainly composed of polyacrylonitrile resins, polyimide resin compositions mainly composed of thermoplastic polyimide resins, polyamide resin compositions mainly composed of polyamide resins, polyethersulfone resin compositions mainly composed of polyethersulfone resins, phenoxy resin compositions mainly composed of phenoxy resins, polypropylene resin compositions mainly composed of polypropylene resins, polycarbonate resin compositions mainly composed of polycarbonate resins, polyethylene resin compositions mainly composed of polyethylene resins, polyester resin compositions mainly composed of polyester resins, acrylonitrile-butadiene-styrene resin compositions mainly composed of acrylonitrile-butadiene-styrene (ABS) resins, polystyrene resin compositions mainly composed of polystyrene (PS) resins, polyphenylene sulfide resin compositions mainly composed of polyphenylene sulfide (PPS) resin compositions, and polyamideimide resin compositions mainly composed of polyamideimide (PAI) resins. From the viewpoints of heat resistance, durability, and processability, polyethersulfone-based resin compositions and polypropylene-based resin compositions are preferred.
[0077] The resin constituting the second resin layer 33 may be the same as or different from the resin constituting the first resin layer 37. From the viewpoint that the second resin layer 33 near the surface does not deform due to heat and maintains its shape as a separator for a fuel cell, it is preferred that the resin constituting the first resin layer 37 is a thermoplastic resin composition and the resin constituting the second resin layer 33 is a thermosetting resin composition.
[0078] From the viewpoint of improving the conductivity of the fuel cell separator member 30, the resin constituting the second resin layer 33 may contain a conductive material. As the conductive material, for example, artificial graphite, natural graphite, carbon black, carbon fiber, carbon nanotube (CNT) can be cited. From the viewpoint of conductivity and cost, artificial graphite and / or natural graphite are preferably used. In addition, the second resin layer 33 may contain conductive short fibers.
[0079] The thickness of the second resin layer 33 is thinner than that of the first resin layer 37. The thickness is preferably 3 to 100 μm, and is preferably 5 to 50 μm from the viewpoint of lightness and processability.
[0080] The graphite layer 31 is substantially formed of graphite. "Substantially formed of graphite" means that the amount of non-conductive material present in the graphite layer 31 is so small that it does not hinder the conductivity of the fuel cell separator member 30. Specifically, it means that the volume resistivity of the graphite is 3 mΩ·cm or less, and the material constituting the graphite layer 31 is composed of 95 wt% or more of graphite.
[0081] The conductive fiber substrate 35 is not particularly limited as long as it is a fiber material having a sheet shape and conductivity. From the viewpoint of improving the strength and elastic modulus of the fuel cell separator component 30, short fibers and non-woven fabrics with conductivity are preferred. The fibers constituting the non-woven fabric can be not only fibers formed by a single type, but also composed of several fibers. As fibers constituting short fibers and non-woven fabrics, for example, chemical fibers such as carbon fibers, glass fibers, polyester, and fibers from minerals such as alumina and silica can be cited. From the viewpoint of heat resistance and chemical resistance, carbon fibers, polyester fibers, and polyphenylene sulfide (PPS) fibers are preferred. From the viewpoint of making the conductivity of the fuel cell separator component 30 good and the viewpoint of improving the elastic modulus of the fuel cell separator component 30, non-woven fabrics formed of carbon fibers are more preferred.
[0082] The conductive fiber substrate 35 constituting the fuel cell separator member 30 is located closer to the surface than the first resin layer 37, thereby preventing cracks from occurring in the fuel cell separator itself when the fuel cell separator member 30 is processed into a fuel cell separator or when the fuel cell is used.
[0083] From the viewpoint of processability, the weight of the conductive fiber substrate 35 is preferably 5 to 200 g / m 2 , more preferably 5 to 50 g / m 2 .
[0084] As another configuration, the fuel cell separator member 30 may have a configuration in which the conductive fiber substrate 35 , the second resin layer 33 , and the graphite layer 31 are stacked in order from near to far from the first resin layer 37 on only one surface of the first resin layer 37 .
[0085] (Method for Manufacturing Fuel Cell Separator Member 30)
[0086] The manufacturing method of the separator component 30 for a fuel cell comprises: a first resin layer forming step, forming a first resin layer composed of a resin; a second resin layer forming step, forming a second resin layer composed of a resin, thinner than the first resin layer, and in a semi-cured state; a conductive fiber substrate laminating step, laminating a conductive fiber substrate on the second resin layer and performing heat compression bonding; a graphite layer forming step, forming a graphite layer on the resin surface of the second resin layer on which the conductive fiber substrate is laminated, wherein the lamination amount of the graphite layer is 50 g / m 2The present invention relates to a method for forming a conductive fiber substrate of a second resin layer, wherein the first resin layer is laminated on the conductive fiber substrate of the second resin layer and heated and pressed. The first resin layer forming step includes: a resin coating step of coating a resin on a film subjected to a demolding treatment; and a resin curing step of forming a first resin layer in a semi-cured state. The second resin layer forming step includes: a second resin coating step of coating a resin on a film subjected to a demolding treatment; and a second resin curing step of forming a second resin layer in a semi-cured state. The graphite layer forming step includes: a graphite sheet lamination step of laminating a graphite sheet formed of graphite on the resin surface of the second resin layer laminated with a conductive fiber substrate and pressing it; and a peeling step of peeling the graphite sheet after the graphite sheet lamination step.
[0087] FIG. 4A to FIG. 4C It is a diagram for explaining a method of manufacturing the separator member 30 for a fuel cell.
[0088] Reference Figure 4A (a) The resin coating process is described. The coating device 401 coats the resin constituting the first resin layer 402 on the release-treated surface of the film 403 subjected to the release treatment. The film 403 can use the same film as the film 205 used in Embodiment 1. The coating device 401 can use the same device as the coating device 201 used in Embodiment 1.
[0089] Reference Figure 4A (a-1) describes the resin curing process. The first resin layer 402 is preferably dried by heating using a dryer. The heating and drying conditions can be appropriately selected according to the thickness of the first resin layer 402. The heating and drying conditions are, for example, 40 to 200° C. and 1 to 120 minutes. The first resin layer 402 after drying is in a semi-cured state (B stage state). Similar to the first resin layer 203, the surface of the resin constituting the first resin layer 402 may be sticky.
[0090] Reference Figure 4A (b) will now describe the second resin coating step. The coating device 409 coats the resin constituting the second resin layer 404 onto the release-treated surface of the film 403 that has been subjected to the release treatment. The coating device 409 can be the same as the coating device 401 in the resin coating step.
[0091] Reference Figure 4A(b-1) describes the second resin curing process. The second resin layer 404 is preferably dried by heating using a dryer. The heating and drying conditions can be appropriately selected according to the thickness of the second resin layer 404. The heating and drying conditions are, for example, 40 to 200°C and 1 to 120 minutes. The second resin layer 404 after drying is in a semi-cured state (B stage state). From the perspective of making the conductivity of the fuel cell separator good and the perspective of increasing the elastic modulus of the fuel cell separator, the thickness of the second resin layer 404 after drying is preferably thinner than the first resin layer 402. Similar to the first resin layer 402, the surface of the resin constituting the second resin layer 404 may be sticky.
[0092] Reference Figure 4B (c) The conductive fiber substrate lamination process is described. In the case of the laminate 420, a conductive fiber substrate 405 is laminated on the resin surface of the second resin layer 404 laminated on the film 403. The laminate 420 is heated and pressurized by a press. Pressing can be performed at room temperature. The conditions for heating and pressurizing can be appropriately selected according to the thickness of the conductive fiber substrate 405 and the thickness of the second resin layer 404. For example, it is 20 to 350°C and 0.1 to 50 MPa. In addition, a roller can be used instead of a press for crimping. As for the crimping conditions, as long as the pressure is such that the conductive fiber substrate 405 is in close contact with the surface of the second resin layer 404. It can be crimping accompanied by heating. In addition, instead of the conductive fiber substrate 405, conductive short fibers formed by, for example, carbon fibers can be evenly sprinkled on the surface of the second resin layer 404, and then pressed.
[0093] Reference Figure 4B (d) describes the graphite sheet lamination process. The film 403 is peeled off from the laminate 420, and a graphite sheet 406 is stacked on the resin surface of the second resin layer 404. Then, the graphite sheet 406 side is crimped using a roller 408. As for crimping, it is preferred to crimp with a pressure that forms a graphite layer when the crimped graphite sheet 406 is peeled off from the resin surface of the second resin layer 404. From the viewpoint of improving the adhesion between the second resin layer 404 and the graphite sheet 406, crimping can be performed while heating. The crimping conditions can be appropriately selected according to the thickness of the graphite sheet 406 and the thickness of the second resin layer 404. For example, the conditions are 20 to 350°C and 0.1 to 50 MPa. In addition to the method using the roller 408, for example, pressurization can be performed using a press machine, or pressurization can be performed while heating.
[0094] Reference Figure 4B(e) The first resin layer lamination process is described. On the surface of the conductive fiber substrate 405 constituting the laminate 430, the first resin layer 402 from which the film 403 is peeled off is laminated. On the resin surface of the first resin layer 402, another laminate 430 is laminated in such a manner that the conductive fiber substrate 405 is in contact with it, and heating and pressurization are performed using a press machine 410. Thus, a laminate 440 in which the first resin layer 402 is laminated on the conductive fiber substrate 405 is obtained. The conditions for heating and pressurization can be appropriately selected according to the thickness of the laminate 440. For example, the conditions are 20 to 350°C and 0.1 to 50 MPa.
[0095] Reference Figure 4C (f) is a description of the peeling step. The peeling step in the method for manufacturing the fuel cell separator component 30 can be performed by peeling the graphite sheet 406 using the same method as the peeling step in the method for manufacturing the fuel cell separator component 10. For example, the graphite sheet 406 can be peeled off only from the end of the stack 440. The graphite sheet 406 is peeled off from the second resin layer 404 so that a portion of the graphite of the graphite sheet 406 remains on the second resin layer 404, forming a graphite layer 407, and obtaining a stack 450. The graphite sheet 406 can be peeled off before the stack 440 is heated and pressurized. Here, the first resin layer 402 corresponds to Figure 3 The first resin layer 37 of the fuel cell separator member 30 is shown. The conductive fiber substrate 405 corresponds to the conductive fiber substrate 35. The second resin layer 404 corresponds to the second resin layer 33. The graphite layer 407 corresponds to the graphite layer 31.
[0096] As another method of forming the graphite layer 407 , the graphite sheet 406 may be wound around the outer circumference of a roller and fixed, and the roller may be used to press the second resin layer 404 . In this way, the graphite layer 407 may be formed on the second resin layer 404 .
[0097] As another method of laminating the conductive fiber substrate, for example, when short fibers are used as the conductive fiber substrate 35, a method of evenly spreading the short fibers on the surface of the first resin layer 37 and laminating the short fibers can be cited. In addition, as another method, the following method can be cited: short fibers are evenly spread on the resin surface of the second resin layer 33, and heating and pressing are performed to obtain a second resin layer 33 with a conductive fiber substrate 35 laminated on one surface of the second resin layer 33. For such a second resin layer 33 with a conductive fiber substrate 35, the second resin layer 33 itself has high strength and high elastic modulus. The fuel cell separator member 30 using the second resin layer 33 with a conductive fiber substrate 35 can be obtained by laminating the second resin layer 33 with a conductive fiber substrate 35 on both surfaces of the first resin layer 37 so that the short fibers are in contact with each other, and heating and pressing are performed.
[0098] Example
[0099] The present invention will be described in more detail by the following examples and comparative examples. However, the present invention is not limited to the following examples.
[0100] Specifically, the following components were used as the components contained in the resin compositions in Examples and Comparative Examples.
[0101] (Material of the first resin layer)
[0102] (1) Main agent A: Cresol Novolac epoxy resin, epoxy equivalent weight 211 g / eq (manufactured by Nippon Kayaku Co., Ltd., EOCN-102S-70),
[0103] (2) Curing agent A: Novolac type phenolic resin, hydroxyl equivalent of 105 g / eq (manufactured by Aica Kogyo Company, Limited, BRG-556),
[0104] (3) Reinforcement agent: phenoxy resin (manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., YP-50),
[0105] (4) Curing accelerator A: 2-undecyl imidazole (manufactured by Shikoku Chemicals Co., Ltd., C11Z),
[0106] (5) Internal mold release agent: carnauba wax (manufactured by Nippon Wax Co., Ltd., carnauba wax No. 1 powder),
[0107] (6) Conductive filler A: artificial graphite, average particle size 25 μm (manufactured by SEC CARBON LIMITED, SGP-25).
[0108] (Graphite Sheet)
[0109] (1) Graphite sheet A: thickness 200 μm, density 1.0 g / cm 3 , volume resistivity is 0.7mΩ·cm (PF-20 manufactured by TOYOTANSO CO., LTD.),
[0110] (2) Graphite sheet B: thickness 40 μm, density 2.0 g / cm 3 , the volume resistivity is 0.1mΩ·cm (artificial graphite sheet).
[0111] (Material of the Second Resin Layer)
[0112] (1) Main agent B: bisphenol A type epoxy resin, epoxy equivalent weight 189 g / eq (Mitsubishi Chemical Corporation, JER828),
[0113] (2) Curing agent A: Novolac type phenolic resin, hydroxyl equivalent of 105 g / eq (manufactured by Aica Kogyo Company, Limited, BRG-556),
[0114] (3) Reinforcement agent: phenoxy resin (manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., YP-50),
[0115] (4) Curing accelerator A: 2-undecyl imidazole (manufactured by Shikoku Chemicals Co., Ltd., C11Z),
[0116] (5) Conductive filler B: acetylene black (DENKA BLACK 100% compressed product manufactured by Denka Corporation).
[0117] (Conductive fiber substrate)
[0118] (1) Carbon fiber nonwoven fabric A: basis weight 10 g / m 2 (Made by Nippon Polymer Sangyo Co., Ltd., CFP-010PV),
[0119] (2) Carbon fiber nonwoven fabric B: basis weight 30 g / m 2 (manufactured by Nippon Polymer Sangyo Co., Ltd., CFP-030PE).
[0120] In Examples and Comparative Examples, sample preparation, evaluation methods, and measurement methods were performed as follows.
[0121] (1) Resin sheet for first resin layer
[0122] (1-1) Resin composition for first resin layer
[0123] 100 parts by mass of the main agent A, 48.8 parts by mass of the curing agent A, and 35 parts by mass of the reinforcing agent were dissolved in methyl ethyl ketone, and then added to a container to prepare a mixed solution. Then, a solution obtained by dissolving 3 parts by mass of the curing accelerator A in methanol, 560 parts by mass of the conductive filler A, and 1 part by mass of the internal mold release agent were added to the mixed solution, and the mixture was stirred well at room temperature, and methyl ethyl ketone was added to control the viscosity within the range of 100 to 3000 mPa·s to obtain a resin composition for a first resin layer.
[0124] (1-2) Resin sheet for first resin layer
[0125] The resin composition for the first resin layer was applied to the demoulding surface of a demoulding-treated film (manufactured by Lintec, PET38X) having a thickness of 38 μm in a manner such that the thickness after drying was 400 μm, and then dried at 70°C for 7 minutes to obtain a resin sheet for the first resin layer. Next, two resin sheets for the first resin layer were stacked in such a manner that the resin surfaces of each other were matched. Then, a laminator (manufactured by Taisei Laminator, VA-700) was used to press the stacked resin sheets at 80°C, 0.4 m / min, and 0.6 MPa to obtain a resin sheet for the first resin layer having a thickness of 620 μm.
[0126] (2) Resin sheet for second resin layer
[0127] (2-1) Resin composition for second resin layer
[0128] 100 parts by mass of the main agent B, 54.5 parts by mass of the curing agent A, and 35 parts by mass of the reinforcing agent were dissolved in methyl ethyl ketone, and then added to a container to prepare a mixed solution. Then, a solution obtained by dissolving 3 parts by mass of the curing accelerator A in methanol and 48 parts by mass of the conductive filler B were added to the mixed solution, and the mixture was stirred well at room temperature, and methyl ethyl ketone was added to control the viscosity within the range of 100 to 3000 mPa·s to obtain a resin composition for a second resin layer.
[0129] (2-2) Resin Sheet for Second Resin Layer
[0130] The resin composition for the second resin layer was applied to the release surface of a 38 μm thick release treated film (PET38X manufactured by Lintec) to a thickness of 20 μm after drying, and then dried at 70° C. for 3 minutes to obtain a resin sheet for the second resin layer.
[0131] (3) Fuel cell separator member 10
[0132] The separator component 10 for fuel cells is manufactured in the following manner. A graphite sheet is bonded to the adhesive surface of an adhesive sheet (SPV tape manufactured by Nitto Denko Corporation). The adhesive sheet is crimped using a laminator at 80°C, 0.4 m / min, and 0.6 MPa. Next, the graphite sheet is peeled off from the adhesive sheet to obtain an adhesive sheet with graphite to which a portion of the graphite sheet is attached. Two adhesive sheets are prepared, and the surfaces of the adhesive sheets to which graphite is attached are bonded to the two surfaces of the resin sheet for the first resin layer from which the film has been peeled off, and crimped at 80°C, 0.4 m / min, and 0.6 MPa. Then, the adhesive sheet is peeled off to obtain a separator component 10 for fuel cells having graphite layers formed on both sides. At this time, the lamination amount of the graphite layer of the separator component 10 for fuel cells is 1.8 g / m 2(single side: 0.9g / m 2 ). It should be noted that the stacking amount of the graphite layer is obtained by the following steps. Prepare a resin sheet for the first resin layer before the graphite layer is set and a resin sheet for the first resin layer after the graphite layer is set. Cut each resin sheet into a square of 10 cm square. Measure the mass of the cut resin sheet respectively. Then, subtract the mass of the resin sheet before the graphite layer is set from the mass of the resin sheet for the first resin layer after the graphite layer is set. The value calculated by dividing the subtracted mass by the area of the sample after cutting is used as the stacking amount of the graphite layer per unit area.
[0133] (4) Fuel cell separator member 30
[0134] The separator component 30 for fuel cells is manufactured in the following manner. First, a carbon fiber nonwoven fabric is stacked on the resin surface of the second resin layer resin sheet, and the laminate is pressed at 100°C, 0.4 m / min, and 0.6 MPa using a laminator. Next, the film is peeled off from the second resin layer resin sheet, and a graphite sheet is stacked on the resin surface. After pressing at 80°C, 0.4 m / min, and 0.6 MPa, the graphite sheet is peeled off to obtain a laminated body stacked in the order of carbon fiber nonwoven fabric / second resin layer resin sheet / graphite layer. At this time, the stacking amount of the graphite layer is 12 g / m 2 Two sheets of the laminate are prepared, and the laminates are respectively laminated on both sides of the resin sheet for the first resin layer in such a manner that the surfaces of the carbon fiber nonwoven fabrics are matched, and pressure bonding is performed under the conditions of 100°C, 0.2 m / min, and 0.6 MPa to obtain a separator component 30 for a fuel cell. It should be noted that, as for the method for determining the lamination amount of the graphite layer in the separator component 30 for a fuel cell, except that the resin sheet for the first resin layer before the graphite layer is provided and the resin sheet for the first resin layer after the graphite layer is provided are changed to the resin sheet for the second resin layer with the carbon fiber nonwoven fabric before the graphite layer is provided and the resin sheet for the second resin layer with the carbon fiber nonwoven fabric after the graphite layer is provided, the same steps as those for determining the lamination amount of graphite in the separator component 10 for a fuel cell are used.
[0135] <Measurement of volume resistivity>
[0136] The conductivity was evaluated by measuring the volume resistivity.
[0137] (1) Preparation of measurement samples
[0138] A fuel cell separator component (sample) cut into 100 mm × 100 mm was prepared. A release agent (RIMRIKEI N-849, manufactured by Chukyo Oil & Fats Co., Ltd.) was applied to a hot plate of a press (manual hydraulic heating press IMC-185B modified by Imoto Seisakusho Co., Ltd.), and the sample was placed on the hot plate and pressed at 180°C, 3 minutes, and 20 MPa to obtain a flat plate sample for measurement.
[0139] (2) Measurement method
[0140] The volume resistivity (mΩ·cm) of the measurement sample was measured by a four-probe method (RM3545, manufactured by HIOKI Electric Co., Ltd.) in accordance with JIS K7194.
[0141] <Measurement of thickness>
[0142] The thickness was measured using a micrometer when preparing a measurement sample. The thickness of the graphite layer was measured using an optical microscope.
[0143] <Measurement of strength>
[0144] (1) Preparation of measurement samples
[0145] The sample produced when measuring the volume resistivity was cut into pieces with a width of 10 mm and a length of 20 mm to prepare a sample for measurement.
[0146] (2) Measurement method
[0147] The test was performed using an Autograph tester (AG-10 manufactured by Shimadzu Corporation). The test was performed using three-point bending (the distance between the supporting points was 10 mm, and the test speed was 2 mm / min) to determine the breaking load. The strength (MPa) was calculated based on the obtained breaking load in accordance with JIS K7171.
[0148] <Measurement of water vapor transmission rate>
[0149] The gas barrier properties were evaluated by measuring the water vapor transmission rate.
[0150] (1) Preparation of measurement samples
[0151] The sample produced when measuring the volume resistivity was cut into a circle having a diameter of 76 mm to prepare a sample for measurement.
[0152] (2) Measurement method
[0153] The water vapor transmission rate (%) was measured according to JIS Z0208 at 40°C and 90% RH per 1m 2 The 24-hour moisture permeability value (g / m 2The evaluation criteria are as follows.
[0154] Excellent: Water vapor transmission rate is less than 13%.
[0155] Good: The water vapor transmission rate is 13% or more and less than 32%.
[0156] Poor: Water vapor transmission rate is 32% or more.
[0157] <Processability>
[0158] The processability was evaluated by visually checking whether or not the resin adhered to the hot plate of the press when the measurement sample was produced by pressing. The evaluation criteria were as follows.
[0159] Good: No resin adheres to the hot plate of the press.
[0160] Poor: Resin adheres to the hot plate of the press.
[0161] <Expansion after processing>
[0162] The processed samples were visually checked for swelling. The evaluation criteria were as follows.
[0163] Good: There is no swelling at all, or swelling occurs but there is no problem in practical use.
[0164] Poor: There is expansion, which is problematic in practical use.
[0165] <Example 1 (a separator member 10 for a fuel cell, having graphite layers on both sides)>
[0166] According to the process of (3) for producing the fuel cell separator member 10 , the fuel cell separator member 10 having the graphite layers formed on both surfaces is produced.
[0167] <Example 2 (a fuel cell separator member 10 having a single-sided graphite layer structure)>
[0168] According to the manufacturing process of the fuel cell separator member 10 (3), the fuel cell separator member 10 having the graphite layer formed only on one surface is manufactured.
[0169] <Example 3 (a separator member 30 for a fuel cell, having graphite layers on both sides)>
[0170] As the carbon fiber nonwoven fabric, the carbon fiber nonwoven fabric A was used, and the fuel cell separator member 30 having graphite layers formed on both surfaces was manufactured according to the manufacturing process of (4) the fuel cell separator member 30 .
[0171] <Example 4 (a separator member 30 for a fuel cell, having graphite layers on both sides)>
[0172] As the carbon fiber nonwoven fabric, the carbon fiber nonwoven fabric B was used, and the fuel cell separator member 30 having graphite layers formed on both surfaces was manufactured according to the manufacturing step (4) of the fuel cell separator member 30 .
[0173] <Comparative Example 1 (Fuel Cell Separator Member 10, No Graphite Layer)>
[0174] According to the process of preparing the resin sheet for the first resin layer (1-2), a resin sheet for the first resin layer having a thickness of about 360 μm was prepared and used as the separator member 10 for the fuel cell without the graphite layer.
[0175] Comparative Example 2 (a fuel cell separator member 10 having a lamination amount of graphite layers exceeding 200 g / m 2 )>
[0176] According to the preparation steps of the resin sheet for the first resin layer (1-2), a resin sheet for the first resin layer with a thickness of 100 μm was prepared. Graphite sheets A were laminated on both sides of the resin sheet and pressed at 80°C, 0.2 m / min, and 0.6 MPa to prepare a single-sided lamination weight of 200 g / m 2 A fuel cell separator member 10 is provided.
[0177] Comparative Example 3 (a fuel cell separator member 10 having a lamination amount of graphite layers exceeding 80 g / m 2 )>
[0178] According to the preparation steps of the resin sheet for the first resin layer (1-2), a resin sheet for the first resin layer with a thickness of 550 μm was prepared. Graphite sheets B were laminated on both sides of the resin sheet and pressed at 80°C, 0.2 m / min, and 0.6 MPa to prepare a single-sided lamination weight of 80 g / m 2 A fuel cell separator member 10 is provided.
[0179] [Table 1]
[0180]
[0181] (*) In Example 2, the film was provided on the surface where the graphite layer was not provided to form the molding.
[0182] From the results in Table 1, it can be seen that the volume resistivity, which is an index of electrical conductivity, of Examples 1 to 4 is lower than that of Comparative Example 1, and the water vapor permeability, which is an index of gas barrier properties, of Examples 1 to 4 is better than that of Comparative Examples 1 and 2. In terms of processability and expansion after processing, all Examples are good. It can also be seen that the strength of Examples 3 and 4 is at least 1.7 times that of the Comparative Example.
[0183] The present invention is considered to be able to implement various embodiments and variations without exceeding the broad purpose and scope of the present invention. In addition, the above-mentioned embodiments are used to illustrate the present invention and do not limit the scope of the present invention. That is, the scope of the present invention is represented by the claims rather than the embodiments. In addition, various variations implemented within the meaning of the claims and equivalent inventions are considered to be within the scope of the present invention.
[0184] This application is based on Japanese Patent Application No. 2020-98939 filed on June 5, 2020. The entire specification, claims, and drawings of Japanese Patent Application No. 2020-98939 are incorporated herein by reference.
[0185] Industrial Applicability
[0186] The fuel cell separator member of the present invention has industrial applicability as a fuel cell separator member.
[0187] Description of Reference Numerals
[0188] 10, 30 Fuel cell separator components,
[0189] 11, 31, 210, 407 graphite layer,
[0190] 13, 37, 203, 402 first resin layer,
[0191] 201, 401, 409 coating devices,
[0192] 205, 403 film,
[0193] 207, 406 graphite sheets,
[0194] 209, 408 rollers,
[0195] 33, 404 second resin layer,
[0196] 35, 405 conductive fiber substrate,
[0197] 410 press machine,
[0198] 206, 220, 420, 430, 440, 450 stacked bodies.
Claims
1. A separator component for a fuel cell, comprising: a first resin layer composed of a resin; and A graphite layer, wherein the material constituting the graphite layer is composed of more than 95 wt % of graphite, Between the first resin layer and the graphite layer, a conductive fiber substrate and a second resin layer composed of a resin are stacked in this order from the first resin layer side. The second resin layer is thinner than the first resin layer. The lamination weight of the graphite layer is 50 g / m 2 Hereinafter, the volume resistivity of the graphite is 3 mΩ·cm or less.
2. The fuel cell separator member according to claim 1, wherein: The resin is a thermoplastic resin composition or a thermosetting resin composition.
3. A method for manufacturing a separator member for a fuel cell, comprising: A first resin layer forming step of forming a first resin layer made of resin; A second resin layer forming step of forming a semi-cured second resin layer made of resin and thinner than the first resin layer; a conductive fiber substrate laminating step of laminating a conductive fiber substrate on the second resin layer and performing heating and pressure bonding; A graphite layer forming step, forming a graphite layer on the resin surface of the second resin layer on which the conductive fiber substrate is laminated, wherein the lamination weight of the graphite layer is 50 g / m 2 Below, and the material constituting the graphite layer is composed of 95wt% or more of graphite having a volume resistivity of 3mΩ·cm or less; and The first resin layer laminating step is to laminate the first resin layer on the conductive fiber substrate of the second resin layer and perform heating and pressurization.
4. The method for manufacturing a fuel cell separator member according to claim 3, wherein: The first resin layer forming step includes: a resin coating step of coating the resin on the film subjected to the mold release treatment; and a resin curing step of forming the first resin layer in a semi-cured state.
5. The method for producing a fuel cell separator member according to claim 3 or 4, wherein: The second resin layer forming step includes: a second resin coating step of coating the resin on the film subjected to the mold release treatment; and a second resin curing step of forming the second resin layer in a semi-cured state.
6. The method for producing a fuel cell separator member according to any one of claims 3 to 5, wherein: The graphite layer forming step includes: a graphite sheet laminating step of laminating and pressing a graphite sheet formed of the graphite on a resin surface of a second resin layer laminated with the conductive fiber substrate; and a peeling step of peeling the graphite sheet after the graphite sheet laminating step.
Citation Information
Patent Citations
Fuel cell separator, and manufacturing method thererof
JP2009129601A
Semiconductor substrate and semiconductor device
JP2020098939A
Fuel cell graphitc composite flow field plate and its manufacturing method
CN101071876A
Bipolar plate for vanadium battery and preparation method thereof
CN108023104A
Separator for fuel cell and its manufacturing method
JP2006210222A